Exploring ventral hernia repair: a comparison and future outlook on laparoscopic versus open techniques - Shahabuddin, M.; Taslima, Ayman (International Journal of Research in Medical Sciences, 2025)
Background: Ventral hernia repair (VHR) is needed due to abdominal wall abnormalities and can be done open or laparoscopically. Minimally invasive laparoscopic surgery may reduce postoperative discomfort, hospital stays, and wound infections. Open repair allows comprehensive exploration and healing but takes longer and has more wound complications. This study seeks to compare the findings of VHR using both laparoscopic and open techniques. Methods: Sixty individuals diagnosed with ventral hernia were included, with 30 undergoing open repair and 30 undergoing laparoscopic repair. Study included individuals diagnosed with ventral hernia, while exclusion criteria involved patients with contraindications for either technique. Data on patient demographics, perioperative complications, postoperative pain, and recurrence rates were collected. Statistical analyse was also accomplished. Results: The mean age of the open repair group was 56 years and the laparoscopic group 52. There were no significant gender, BMI, or comorbidity differences across groups. Laparoscopic repair led to reduced discomfort after surgery (p<0.05), shorter hospital stays (mean: 3.6 vs. 4.5 days, p=0.001), and fewer wound infections (10% vs. 13%, p=0.548). Recurrence rates were modest and comparable (3% laparoscopic vs. 7% open, p=0.621). Conclusions: Laparoscopic VHR (LVHR) offers significant advantages over open repair, including reduced postoperative pain, shorter hospital periods, and fewer wound infections. Both techniques have comparable recurrence rates, but the laparoscopic approach generally provides better postoperative outcomes.